Efeitos de Programas de Pliometria e Carga Ótima de Trabalho em Jovens Jogadores de Futebol de Elite - Luís Filipe Lopes Teixeira (2017)
This professional internship report was held in the 2nd Cycle in Sport for Children and Young People in the Sports University of Porto, in the Sub-19 team of Sporting Clube de Braga, which participated in the National Juniors Championship. The accomplishment of this stage allowed us to understand and experience the reality of high performance, namely the planning, the operationalization and control and evaluation of the training process. This way, this essay intends, in addition to reporting the experiences of the club during the internship period, to critically analyze the work processes involved. In addition, it was tried to base the work process with bibliographical revision that corroborated it. The match is marked by a frequent demand for high-intensity efforts and, therefore, it was considered important to carry out, at this stage, a study in the area of physical optimization. We attempted to study two models of the optimization of lower limb strength, plyometric training and training with optimum power load, where we observed and evaluated the effects of the programs in improving speed, vertical impulsion and agility during twelve guided training sessions. In both training programs there were improvements in the vertical impulsion, with a moderate positive effect at CMJ (g = 0.94 at TP and g = 1.09 at TOC). In SJ, the TOC program had a large positive effect (g = 1.4), whereas TP was not as effective in improving the performance of this test, presenting a moderate positive effect (g = 1.01). Both groups had moderate positive effects on the development of V 10M (g = -0.29 on TP and g = -0.37 on TOC). However, in V 30M the TOC proved to be more effective, presenting a moderate positive effect (g = -0.83), while the TP had small effect improvements (g = -0.23). Finally, in agility, both programs presented a moderate and positive effect (g = -0.62 in TP and g = -1.11 in TOC). Was concluded that the two models allowed to improve the performance of vertical thrust, speed and agility.